Sharing the Bandwidth in Cognitively Overloaded Teams and Systems: Mechanistic Insights from a Walk on the Wild Side of Clinical Reasoning. Issue 2 (15th March 2022) - Boyle, James G.; Walters, Matthew R.; Jamieson, Susan; Durning, Steven J.
Abstract: IssuePrevious work from the diagnostic error literature has provided indirect evidence that faulty clinical reasoning may be the most frequent cause of error when attaching a diagnostic label. The precise mechanisms underlying diagnostic error are unclear and continue to be subject to considerable theory informed debate in the clinical reasoning literature. Evidence: We take a theoretical approach to merging these two worlds of literature by first zooming out using distributed cognition as a social cognitive lens (macro theory) to develop a view of the process and outcome of clinical reasoning occurring in the wild – defined as the integrated clinical workplace – the natural habitat of clinicians working within teams. We then zoom in using the novel combination of cognitive load theory and distributed cognition to provide additional theoretical insights into the potential mechanisms of error. Implications: Through the lenses of distributed cognition and cognitive load theory, we can begin to prospectively investigate how cognitive overload is represented and shared within interprofessional teams over time and space and how this influences clinical reasoning performance and leads to error. We believe that this work will help teams manage cognitive load and prevent error.